2014
DOI: 10.4103/0301-4738.109513
|View full text |Cite
|
Sign up to set email alerts
|

Implantation of iris-claw Artisan intraocular lens for aphakia in Fuchs′ heterochromic iridocyclitis

Abstract: Implantation of iris-claw Artisan intraocular lens (IOL) is a surgical option for correction of aphakia; however, these IOLs have not been used in eyes with uveitis including Fuchs’ heterochromic iridocyclitis (FHI) due to possible risk of severe postoperative intraocular inflammation. In the case reported here, we secondarily implanted an Artisan IOL in a 28-year-old man with FHI who had aphakia with no capsular support due to a previous complicated cataract surgery. Enclavation was easily performed and no in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 9 publications
0
2
0
Order By: Relevance
“…A patient with Fuchs' heterochromic iridocyclitis achieved a BCVA of 20/20 one month postoperatively, although a few deposits on the IOL surface were noted. The IOL remained stable with no subsequent iris atrophy, subluxation, or pupil ovalization, and glaucoma, vitreous inflammation, or clinical cystoid macular oedema were not observed (22). Li et al observed that combined coreoplasty and Artisan IOL implantation in post-traumatic vitrectomized aphakic eyes enhanced the visual acuity of the patients without significantly affecting IOP (23).…”
Section: Outcomes and Complications Following Implantation Of Ac Iolsmentioning
confidence: 99%
“…A patient with Fuchs' heterochromic iridocyclitis achieved a BCVA of 20/20 one month postoperatively, although a few deposits on the IOL surface were noted. The IOL remained stable with no subsequent iris atrophy, subluxation, or pupil ovalization, and glaucoma, vitreous inflammation, or clinical cystoid macular oedema were not observed (22). Li et al observed that combined coreoplasty and Artisan IOL implantation in post-traumatic vitrectomized aphakic eyes enhanced the visual acuity of the patients without significantly affecting IOP (23).…”
Section: Outcomes and Complications Following Implantation Of Ac Iolsmentioning
confidence: 99%
“…[5678] At times, when placement of the primary IOL becomes difficult due to deficient posterior capsular support, secondary IOLs come in hand to provide some useful vision to these patient's. [9101112] In terms of intraocular stability and visual acuity, the glued IOL has shown to provide better outcomes in non-uveitic eyes with deficient capsules. [13141516] The implantation of a glued trans-scleral fixated posterior chamber IOL poses a major challenge to the surgeon when the vascular coats of the eye have already suffered the brunt of an inflammation.…”
mentioning
confidence: 99%